Reconocemos las partes del cuerpo humano - Leandro Méndez de Hidalgo, Bertha Regina (2018)
Every day we share with our students ideas, experiences, occurrences that allow them to learn from their environment and their needs. The area of Science and Environment allows students to develop scientific thinking to understand and apply science and technology for the benefit of humanity. _x000D_ The first chapter is intended for the demonstration of strategies that will be developed in each of the pedagogical processes in the learning session called "We recognize the parts of the human body"._x000D_ In the second chapter the foundation of the area of science and environment is exposed according to the learning routes in addition to the theoretical sustenance, taking into account the definition of the inquiry.